2012
DOI: 10.1017/s1368980012000158
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in healthy Romanian caregivers and risk of respiratory infections

Abstract: Conclusions: Vitamin D status is alarmingly poor in active, relatively young women residing in Romania. If our results are reproduced by other investigations, action to improve vitamin D status at the population level is necessary. We were not able to show a statistically significant relationship between vitamin D status and infection risk in our material. Keywords Vitamin D Romania Infections riskThe important role of vitamin D in Ca metabolism and bone health is well accepted (1) . The discovery that most hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…The poor vitamin D status was found recently also in young women residing in Romania. 37 More extensive studies on vitamin D status in the Romanian population are required owing to the possibility that the poor vitamin D status could be a problem in the national health.…”
Section: Discussionmentioning
confidence: 99%
“…The poor vitamin D status was found recently also in young women residing in Romania. 37 More extensive studies on vitamin D status in the Romanian population are required owing to the possibility that the poor vitamin D status could be a problem in the national health.…”
Section: Discussionmentioning
confidence: 99%
“…Wayse et al 134 Laaksi et al 135 Ginde et al 136 Roth et al 137 Jartti et al 138 Sabetta et al 139 Freishtat et al 119 Berry et al 140 Camargo et al 31 Morales et al 124 Hirani et al 141 Science et al 142 Aregbesola et al 143 Gale et al 45 McNally et al 144 Porojnicu et al 145 patients, 17,53 suggesting that compensatory mechanisms exist to counter any effects of vitamin D enhancement of T H 2 responses. For example, increased IgE-mediated sensitization to common allergens, such as peanut, ragweed, and oak, has been observed in vitamin D-deficient children.…”
Section: Respiratory Tract Infectionsmentioning
confidence: 99%
“…Several observational studies have evaluated the role of serum 25-hydroxyvitamin D (25(OH)D) concentration in respiratory tract infections [16][17][18][19][20][21][22][23][24][25]. However, all these studies have important limitations including short follow-up period [16], small sample size [16-20, 24, 25], case-control design [18][19][20], or crosssectional design with retrospective ascertainment of symptoms [21,22] and failure to obtain laboratory confirmation of self-reported illness [16,[21][22][23]. The studies in adults have shown an association between lower vitamin D levels and increased respiratory infections (self-reported) [21,22,24] and absence from work due to respiratory symptoms [23].…”
mentioning
confidence: 99%